EASTERN PARTNERSHIP: A NEW STAGE IN THE DEVELOPMENT OF EUROPEAN UNION RELATIONS WITH THE POST-SOVIET COUNTRIES - L. Chuvakhina (Вестник университета)
The issues of development of the Eastern Partnership created at the initiative of the European Union (EU) for the development of integration relations with the countries of the post-Soviet area are discussed. The program of the cooperation includes the Eastern European and Caucasian states. The Eastern Partnership is aimed at the conclusion by the countries of the post-Soviet area the agreements on association with the EU. Cooperation in the framework of the Eastern Partnership is focused on such priority areas as economic development, strengthening governance institutions, development of relations in the field of energy, expansion of contacts between people. In relations with partner countries the EU proceeds from a policy of differentiated approach to each individual country. It is concluded that the development of relations within the framework of the Eastern Partnership will occur against the background of the deterioration of relations between Russia and Western countries.